POTENTIAL SUNSCREEN OF ETHANOLIC EXTRACT OF CLOVE HERB (Syzygium aromaticum L.) AND BROTOWALI (Tinospora crispa L.) - Anggoro, Aloysius barry; Eliza, Novi; Dian Advitasari, Yustisia; Sulistiyanto W.S, F.X. (Dian Nuswantoro Semarang, 2024)
Inflammation, erythema, pigmentation, hyperplasia, immunosuppression, and chronic effects includingphotocarcinogenesis and premature aging are the consequences that can be caused by UV B radiation fromsunlight. This skin damage can get worse and cause DNA damage if the skin is not properly protected. Theaim of this research is to evaluate the light protection factor (SPF) of ethanol extracts of clove and brotowaliherbs using UV-vis spectrophotometry. Evaluate the SPF value using various concentration levels rangingfrom 100, 200, 300, 400 and 500 ppm for each extract. The SPF value is calculated using the Mansurequation, measured from 290-320 nm with an interval of 5 nm. The SPF value obtained from clove herbethanol extract was 2.741; 5,827; 7,895; 10,341; and 13,132, while the ethanol extract of brotowali herb was3,382; 7,166; 10,198; 13,420; and 18,061. The results show that both extracts have considerable potential formaking sunscreen preparations.